Musculoskeletal pain and its association with health status, maturity, and sports performance in adolescent sport school students: a 2-year follow-up - Julia S. Malmborg; Ann Bremander; Stefan Bergman; Emma Haglund; M. Charlotte Olsson (BMC, 2022)
Abstract Background Musculoskeletal pain and its risk factors are rarely assessed in studies on adolescent athletes. The aim was to identify risk factors at baseline that were associated with the persistence or development of musculoskeletal pain at a two-year follow-up in adolescent sport school students, and to study cross-sectional associations at follow-up between musculoskeletal pain and sports performance. Methods Sport school students (79 boys and 52 girls, aged 14 years at baseline) were divided into infrequent (never-monthly) or frequent (weekly-almost daily) pain groups, based on frequency of pain using a pain mannequin. Logistic regression analyses were performed to study longitudinal associations between frequent pain at follow-up and baseline variables: pain group, number of regions with frequent pain, health status by EQ-5D, maturity offset (pre, average, or post peak height velocity), and sports (contact or non-contact). Linear regression analyses were used to study cross-sectional associations between pain groups and 20-m sprint, agility T-test, counter-movement jump, and grip strength at follow-up. Results were stratified by sex. Results A higher percentage of girls than boys reported frequent pain at follow-up (62% vs. 37%; p = 0.005). In boys, frequent pain at follow-up was associated with being pre peak height velocity at baseline (OR 3.884, CI 1.146-13.171; p = 0.029) and participating in non-contact sports (OR 3.429, CI 1.001-11.748; p = 0.050). In girls, frequent pain at follow-up was associated with having frequent pain in two or more body regions at baseline (OR 3.600, CI 1.033-12.542; p = 0.044), having a worse health status at baseline (OR 3.571, CI 1.026-12.434; p = 0.045), and participating in non-contact sports (OR 8.282, CI 2.011-34.116; p = 0.003). In boys, frequent pain was associated with worse performances in 20-m sprint and counter-movement jump, but not in agility T-test and grip strength. Conclusions Baseline risk factors for having frequent pain at follow-up were late maturation in boys, frequent pain and worse health status in girls, and participation in non-contact sports in both sexes. Boys with pain performed worse in sports tests. Coaches and school health-care services should pay attention to the risk factors and work towards preventing pain from becoming persistent.